Optimization of Local Materials in the Water Purification System as an Effort to Reduce Iron Content in Water Sources “Sumber Lestari” in the Manduro Village, Jombang District - Elly Setyowati; Indasah Indasah (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Background. Groundwater is the main source of drinking water in many countries around the world. It is an essential source of water for domestic, industrial and agricultural activities. In this research, groundwater was collected from Manduro village, Kabuh district, Jombang city. Iron sometimes referred to as “fly in the ointment” has been one of the most troublesome domestic water contaminants. Various quantities of iron are often present in water because of large amounts of iron present in the soil and because corrosive water will pick up iron from pipes clothing washed in water containing excessive iron may become stained with a brownish colour. Iron deposits may build up in tanks, water heater and pipelines reducing the quantity and quality of water. Iron can be present in several forms, and each form can potentially require a different method of removal. The study aims to develop a cheap and easy technology to reduce the presence of excess iron in groundwater. Methods. The iron removal system is developed by slow sand filter and selecting coconut husk fibre as the substrate material of filter media. The filter media made from coconut husk fibre 15 cm, plain sand 15 cm, coconut husk fibre 20 cm, plain sand 20 cm, charcoal 15 cm, grave 10 cm and mineral stones 15 cm. The developed technique seemed to be very effective in reducing the iron concentration below 0.3 ppm as required Permenkes RI No. 492/MENKES/PER/IV/2010. Result. The research result show that filter media could reduce iron content. The efficiency of the filter media in reduce of iron content is about 71 - 96%. Conclusions. Media filter is effective for reduce iron content in groundwater up to 96% and has fulfilled Permenkes RI No. 492/MENKES/PER/IV/2010 Implication. This method can be applied to people who has the same problem. We can counseling how about made filter media to reduce iron content.